Use of silver-impregnated umbilical venous catheters for prevention of catheter associated bloodstream infection in neonates (Annals of Medical Research, 2021)
Aim: Neonates hospitalized in neonatal intensive care units (NICU)s often require a venous access. Umbilical venous catheter (UVC) is the commonly used one. UVCs are known to cause life-threatening complications such as catheter-associated bloodstream infections  (CABSI). To the best of our knowledge, our unit is the first and only NICU in Turkey that used silver-impregnated UVCs. This study aims to evaluate the impact of silver-impregnated UVC insertion on the incidence of CABSI.Materials and Methods: A total of 108 patients were included in this retrospective study. After the application of exclusion criteria, the control group was composed of neonates (n=58) who had polyurethane (PU) UVCs inserted and the study group consisted of infants (n=41) who had silver-impregnated UVCs inserted. Demographic and clinical data of the mothers and neonates including duration of UVC insertion and sepsis incidence were collected and compared statistically. Results: There was no statistically significant difference between the groups except for intubation period and mortality. One neonate in each group had CABSI (p=1). Four neonates, two in each group, were diagnosed with clinical sepsis. Total CABSI incidence in our whole population was 2% and 3.3 per 1000 catheter days.Conclusion: Strict precautions should be taken to prevent infection in every unit. In NICUs with low incidence of sepsis, silver-impregnated UVCs may have no further effect in the reduction of CABSI.